2012
DOI: 10.1108/20425941211250543
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Kamut® wheat quality

Abstract: Purpose -The purpose of this paper is to investigate the potential quality of Kamut s (triticum turgidum turanicum) as an ancient relative of modern durum wheat for food preparation and Egyptian consumption. Design/methodology/approach -The methodology included in this paper is based on quality evaluation of Kamut wheat of the Dashure-Fayume geographical origin physically, chemically and technologically compared to Beni Suef 1, Beni Suef 3 and Suhag 3, the most dominant durum varieties in Egypt. After that, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The cocatalyst can afford trapping sites for the photogenerated carriers and promote carrier separation to improve the performance of the semiconductor photocatalyst, thus enhancing the quantum efficiency . Most importantly, the cocatalysts deposited on the surface of the semiconductor photocatalyst accelerate the reactions through lowering the activation energy. , Many reported studies have confirmed that the photocatalytic activities can be significantly enhanced by composing suitable cocatalysts on the semiconductor photocatalysts. The cocatalysts mainly include the oxidation cocatalysts (RuO 2 , RhO x , IrO 2 , MnO x , CoO x , etc .)…”
Section: Strategies To Improve Photocatalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The cocatalyst can afford trapping sites for the photogenerated carriers and promote carrier separation to improve the performance of the semiconductor photocatalyst, thus enhancing the quantum efficiency . Most importantly, the cocatalysts deposited on the surface of the semiconductor photocatalyst accelerate the reactions through lowering the activation energy. , Many reported studies have confirmed that the photocatalytic activities can be significantly enhanced by composing suitable cocatalysts on the semiconductor photocatalysts. The cocatalysts mainly include the oxidation cocatalysts (RuO 2 , RhO x , IrO 2 , MnO x , CoO x , etc .)…”
Section: Strategies To Improve Photocatalytic Performancementioning
confidence: 99%
“…Sustainable development requires the growth of practical and clean energy to avoid subsequent environmental problems . Solar energy is a clean energy and is generally accepted as an abundant, endless, and renewable source that meets the current and future energy needs of humans. , The semiconductor photocatalyst is an ideal candidate in solar energy applications, as it can efficiently utilize solar energy with simultaneous energy conversion and environmental remediation. The energy conversion aspect mainly includes hydrogen evolution, CO 2 reduction, nitrogen fixation, and oriented synthesis to fulfill the sustainable strategy.…”
mentioning
confidence: 99%
“…sakei is known to break down proteins during fermentation to synthesize amino acids and other useful substances [32]. Kamut contains about 75% carbohydrates and 18% protein [5], and it was determined that these two microorganisms can effectively utilize compounds in KaS, and have a high potential to increase the efficacy of the fermentation process.…”
Section: Discussionmentioning
confidence: 99%
“…The most common types of wheat are Triticum durum, Triticum spelta, Triticum carthlicum, Triticum aestivum, and Triticum turanicum (khorasan wheat) [1][2][3]. Among them, khorasan wheat, also known as kamut, is found in food products, and has gained popularity owing to its health benefits, including its anti-inflammatory and anti-oxidant efficacy in kamut cookies, as well as its beneficial effects on diet, compared with modern wheat [4][5][6]. The thousand-year-old khorasan wheat species contains various physiologically active substances such as selenium, β-glucan, GABA, as well as positive health effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…The taste of khorasan is sweet and grassy and can be described as a combination of raw sweet corn and freshly cut lawn with a milky undertone [ 88 ]. An Egyptian study revealed that kamut couscous was highly favored by the participants, who described its taste as tasty, buttery, crunchy, and delicious, so it has many taste advantages [ 89 ]. Kamut is used in a wide variety of food products, including cereals, breads, cookies, snacks, pancakes, bread mixes, bulgur, pasta, and baked goods [ 90 ].…”
Section: Statistical Analysis Of Sensory Datamentioning
confidence: 99%